Estetika Tari Sipatmo sebagai Pengembangan Modul Projek Penguatan Profil Pelajar Pancasila pada Kurikulum Merdeka dalam Pembelajaran Seni Tari - Nabillah Maharani; Deden Haerudin; Ida Bagus Ketut Sudiasa (Program Studi Pendidikan Tari FBS UNJ, 2024)
The changes in movement and function that were once dances for welcoming ceremonies have become ballroom dances are imbued with the aesthetics of Sipato Modernism. this research focuses on: how Sipatomo uses her dance aesthetics as a teaching module for Pencasilla students to study the art of dance. the theory used in this study is teaching material theory, which is considered to be related to aesthetic theory. this study uses a descriptive qualitative approach. data collection strategies were conducted through interviews, observations and literature review and were processed according to research objectives.